Changes in parent-assessed oral health-related quality of life among young children following dental treatment under general anaesthetic - Malden PE, Thomson WM, Jokovic A, Locker D. (Blackwell Synergy, 2008)
To estimate the nature and magnitude of changes in oral health-related quality of life (OHRQoL) among children having dental treatment under general anaesthetic (GA) and to examine the evaluative properties of the Child Oral Health-related Quality of Life Questionnaire (COHQOL )